KNOWLEDGE MANAGEMENT: WHY DO WE NEED IT FOR CORPORATES - G., Bhojaraju (Malaysian Journal of Library and Information Science, 2005)
This article gives a brief introduction about Knowledge Management (KM), its need, definition, components, KM assets, challenges and processes of KM initiative at any organisation. It also provides a narration on how the KM initiative has been adopted at ICICI OneSource, to support the achievement of its Business Process Outsourcing objectives. Both knowledge sharing as well as re-use need to be encouraged and recognized at the individual employee level as well as the company level. This is best done by measuring and rewarding knowledge-performance. Sustained strategic commitment and a corporate culture that is conducive to knowledge-performance are vital for success in Knowledge Management. The paper concludes with suggestions for the implication for policy and future practices